Measuring what matters in value-added trade - Borin, Alessandro; Mancini, Michele (Economic systems research, 2023)
The spread of global value chains (GVCs) has given rise to new statistical tools, the inter-country input-output tables, and new analytical frameworks aimed at properly identifying production linkages between and within economies. However, several important questions remain unaddressed. This paper proposes a new toolkit for value-added accounting of trade flows at the aggregate, bilateral, and sectoral levels. The paper shows how different empirical issues require distinct accounting perspectives and maps these methodologies onto the economic questions they are best suited to address. We provide novel accounting perspectives that allow us to properly address important empirical issues. With respect to other accounting methodologies previously proposed in the literature, we offer more accurate or, in some cases, more exhaustive value-added decompositions of trade flows (e.g. by covering both domestic and foreign value-added). In addition, the paper gathers a significant amount of the related literature under one comprehensive framework.